THE AT (THE AMAZING TECHNOLOGY) MEMPERKENALKAN WILAYAH MARITIM DAN POTENSI DAERAH PROVINSI KEPULAUAN RIAU MENGGUNAKAN VISUAL VIDEO DAN BERBASIS ANDROID SEBAGAI MEDIA PENGUATAN PENGETAHUAN ANAK SEKOLAH DASAR DI PESISIR - Deny Nusyirwan; Muhammad Bayu Purnama; Muhammad Abyan Fadillah; Prasetya Perwira Putra Perdana; Allysia Shafira; Sulthan Syarif Hanisetya Putra; Dimas Nugroho Putro (UPPM Politeknik Gorontalo, 2019)
Kepulauan Riau (Kepri) is the 32nd province in the Republic of Indonesia which is determined by the DPRRI based on the Constitution No. 25 with Tanjungpinang as the capital city. According to the Kepulauan Riau Health and Stastistic Agency in 2016 the Kepulauan Riau Province had 253,420 km2 consisting of an ocean area of 242,825 km2 (96%) and land area of 10,595.41 km2 (4%). From these data, it is expected that the coastal areas should be able to become a mainstay of the Kepri community's income sources. With the unique potential and economic value, it will be an attraction to disturbances and threats. Therefore, it is necessary to strengthen human resources in coastal areas through education. The life patterns of coastal communities certainly require a different approach to be able to improve education and knowledge of coastal communities, the technology-based solution proposed is The-AT (The Amazing Technology), introduce the maritime region and the potential of the kepulauan riau using visual video and android as a medium to strengthen the knowledge of elementary school children on the coast. The-AT applies games for childrens, which begins with the game showing a map of the area through a gopro camera, then the students are asked to name the island and the location and potential commodities of the area. Android, video and audio will be displayed about the area as information to students who cannot answer correctly. This technology is an effective solution in the formation of thinking patterns for elementary school children regarding the islands in the Kepulauan Riau, so that the formation of a sense of familiarity and a sense to build the potential that exists in the area. At the end it will initiate the technopreneur in the future.